Structural and material properties of bone tissue and fracture risk - Filip, Rafał (Reumatologia/Rheumatology, 2007)
In spite of the fact that no linear relationship is observed between an increase in the BMD value and the reduction of fracture risk, the measurement of bone density still remains an important final evaluation point in the majority of clinical examinations. Frequently, this is also the only criterion for the assessment of the efficiency of anti-osteoporosis treatment. This situation is due to the fact that there is still a lack of non-invasive methods evaluating any material or structural parameters of the bone tissue. In clinical practice, evaluation of other “non-bone” factors of fracture risk, such as family history taking, concomitant diseases, and nutritional and environmental risk factors, remains very important. The study discusses the primary issues concerning structural, e.g. micro-architecture, and material properties of bone tissue, as well as their importance in determining the risk of osteoporotic fractures.